PLANTING OF STIMULATED CORN SEEDS AT DIFFERENT DATES IN SPRING SEASONS - M. M. Khudhair; J. H. Hamza; H. Z. Rihan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate the appropriate planting date and tolerance to adverse growing conditions in the spring season through seeds stimulation technology. A field experiment was carried out in the spring seasons of 2022 and 2023 according to a randomized complete block design in a split-plot arrangement with four replications. The main factor is planting dates (February 15th, March 1st and 15th, and April 1st and 15th). The secondary factor is seeds stimulation (potassium nitrate 6 mg L-1 + licorice extract 6 g L-1, as well as soaking with distilled water only). The stimulated seeds (potassium nitrate + licorice extract) and the planting date of February 15th were superior in traits of fertility ratio, number of grains per ear, weight of 300 grains, total grains yield, biological yield, and harvest index in both seasons (2022 and 2023). The stimulated seeds (potassium nitrate + licorice extract), planted on February 15th, excelled in the traits above (95.6 and 97.7%), (640.7 and 816.9 grain ear-1), (76.19 and 82.69 g), (7.2 and 7.8 ton ha-1), (17.5 and 18.9 ton ha-1) and (41.5 and 41.2%) in both seasons, respectively. It can be concluded that seeds stimulation improved the yield and its components of corn crop under a wide range of environmental conditions, and that planting the stimulated seeds on February 15th contributed to take advantage of the prevailing environmental conditions and regulating the relationship between source efficiency and sink capacity to obtain the highest grain yield. It can be recommended that soaking the seeds with potassium nitrate 6 mg L-1 + licorice extract 6 g L-1 together when planting in mid-February in the spring season to increase grains yield.